William Brown and Freeman Pepper papers - Brown, William, of Lowell, Mass.; Pepper, Freeman
Correspondence, deeds, indentures, receipts, and other papers of Brown and Freeman Pepper, of Ware, Mass., relating chiefly to their land transactions.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Land tenure -- Massachusetts; Lowell (Mass.) -- History; Ware (Mass.) -- History